A characterization of annular domains by quadrature identities. Issue 3 (27th February 2019) - Gardiner, Stephen J.; Sjödin, Tomas
Abstract: This note verifies a conjecture of Armitage and Goldstein that annular domains may be characterized as quadrature domains for harmonic functions with respect to a uniformly distributed measure on a sphere.